2006
DOI: 10.1111/j.1365-2095.2006.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on tailoring of fillet iodine concentrations in adult Atlantic salmon (Salmo salar L.) through dietary supplementation

Abstract: The present study was performed to assess to what degree supplemented dietary iodine (I) was retained in selected tissues, including the fillet of adult Atlantic salmon (Salmo salar) reared in sea water. Atlantic salmon weighing approximately 1.5 kg were randomly assigned to three net pens per treatment and fed moist pellets (based on minced saithe and herring) supplemented with 0, 40 or 80 mg iodine (as KI) kg−1 on dry weight basis for 150 days. The iodine concentrations in the experimental feeds were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The I level in both liver and kidney was close to five times higher compared to muscle and whole body. This is in line with Julshamn et al [ 45 ], who described lower incorporation of I in muscle than in liver and kidney of Atlantic salmon that had been raised for 150 days in seawater and fed 54 or 86 mg I kg −1 diet. In accordance with the present results, experiments with rainbow trout in freshwater have shown increased I levels in the fish after feeding different seaweeds and that the I concentration in muscle was dependent on the dietary level of I and the length/percent body weight increase obtained [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…The I level in both liver and kidney was close to five times higher compared to muscle and whole body. This is in line with Julshamn et al [ 45 ], who described lower incorporation of I in muscle than in liver and kidney of Atlantic salmon that had been raised for 150 days in seawater and fed 54 or 86 mg I kg −1 diet. In accordance with the present results, experiments with rainbow trout in freshwater have shown increased I levels in the fish after feeding different seaweeds and that the I concentration in muscle was dependent on the dietary level of I and the length/percent body weight increase obtained [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…The difference may be due to a higher fat content in muscle of farmed halibut compared to wild halibut, but may also be caused by a low iodine content or bioavailability in the fish feed used for Atlantic halibut in fish farms. For salmon, it has been shown that fish muscle is responsive to iodine supplementations in feed to a certain degree ( 24 ). Furthermore, there was a general trend of declining concentrations of iodine in fish feed in Norway during 2000–2006, probably due to reduced use of fish meal in feed production ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Within this scenario, a new perspective towards consumers' dietary needs must be considered when designing aquafeeds. Fillets traits have already been effectively changed by modulating fish feeds in terms of bioactive fatty acids (Kennedy, Bickerdike, Berge, Dick & Tocher, 2007;Ramos et al, 2008;Rosa, Andrade, Bandarra & Nunes, 2010), selenium (Lorentzen, Maage & Julshamn, 1994;Schram, Schelvis-Smit, Van Der Heul & Luten, 2010) and iodine (Julshamn, Maage, WaagbØ, & Lundebye, 2006;Ramalho Ribeiro et al, 2015). However, the efficacy of muscle fortification seems to be dependent on supplemental dose, feeding strategies and also important the supplement product form (inorganic vs. organic).…”
Section: Introductionmentioning
confidence: 99%